Select Bibliography on Copyright in Relation to Libraries - Desidoc, Director (DESIDOC Journal of Library & Information Technology, 2003)
This bibliography on copyright and intellectual Property Resources is compiled from the reply to a query copyright and libraries, from webcrawler (http://www.webcrawler.com).There are also some other documents available on the net.Since the comprehensive list is very long.one file which is a compilation of bibliography is compiled by Terry kuny,global village Reserach,Ottwa,Ontario (Contact e-mail:terr.kuny@is.com or phone: 613-234-9621). http://dx.doi.org/10.14429/dbit.16.6.3291